Silk Fibroin/Nano-CaP Bilayered scaffolds for osteochondral tissue engineering - Yan, Leping (2014)
In this study, bilayered silk and silk/nano-CaP scaffolds were developed for osteochondral (OC) tissue engineering. Aqueous silk solution (16 wt.%) was used for preparation of the cartilage-like layer and, for generation of the silk/nano-CaP suspension and the bottom layer (CaP/Silk: 16 wt.%). The scaffolds were formed by using salt-leaching/lyophilization approach. The scanning electron microscopy revealed that the both layers presented porous structure and integrated well. Micro-computed tomography images confirmed that the CaP phase was only retained in the silk/nano-CaP layer. The hydration degree and mechanical properties of the bilayered scaffold were comparable to the ones of each single layer. The apatite crystal formation was limited to the silk/nano-CaP layer, when soaking the scaffold in a simulated body fluid solution, which is a must for the application of the developed scaffolds in OC tissue engineering